Kebaya feminism; Political strategies in the works of Indonesian women writers - Priyatna, Aquarini (UI Scholars Hub, 2023)
This article attempts to show and map the feminist agenda in the writings of Indonesian women writers. Focusing on selected prominent Indonesian women writers whose works can be categorized as articulating feminist ideas and perspectives, namely Suwarsih Djojopuspito, Nh Dini, Oka Rusmini, Ratih Kumala, and Intan Paramaditha, I demonstrate how these writers question and examine cultural attributes as a crucial part of gender construction in their works. This article only focuses on writing in prose. By investigating how these writers articulate themselves and how women are written in[to] their works, this research elaborates on women’s writing as rebellion and protest and offers, even provokes gender transgression. Responding to their specific backgrounds and in light of the political and cultural development, the selected writers display protest against and deviance from the patriarchal norms and collectively contribute to the formation of what I coin kebaya feminism, namely feminism that is deeply rooted in Indonesian culture, but accommodates with agility to ideas in the intersections with other cultures.